Murder Was Not a Crime : Homicide and Power in the Roman Republic - Anderson, Eric Gary, 1960- (Book collections on Project MUSE., 1999)
Explores a range of conceptions of the Southwest as reflected in American Indian literature and its interactions with, and interpretations by, Anglo literature.